Phylogeny and Classification of Euglenophyceae: A Brief Review - Bicudo, Carlos E. de M.; Menezes, Mariângela (Frontiers in Ecology and Evolution, 2016)
Euglenophyceae (phototrophic euglenids) are an important lineage within the Euglenida, Euglenozoa. Most of the approximately 3,000 described species are free-living, phototrophic, unicellular flagellates with one to several plastids of secondary origin, three bounding membranes and chlorophylls a and b; but, the lineage also includes colorless species that lost their photosynthesizing capability. They show a typical cell membrane consisting of parallel proteinaceous strips and microtubules located underneath the plasma membrane, and discoid mitochondrial cristae. Euglenozoa are a monophyletic group that includes, besides Euglenida, the Kinetoplastidea, Diplonomea and Symbiontida. Since the class Euglenophyceae was proposed, its classification system has undergone several revisions, mainly after the adoption of molecular techniques. This article summarizes recent advances in the phylogeny and classification of the phototrophic euglenids, aiming at understanding the situation of the group within the phylum Euglenozoa, as well as its evolutionary relationships and the changes in its taxonomic classification. The current status of the group, as well as the limitations derived from the lack of inclusion of tropical strains in phylogenetic studies is briefly discussed.